2017
DOI: 10.1016/j.ctrv.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of concurrent stereotactic radiotherapy and targeted therapy or immunotherapy: A systematic review

Abstract: This review gives a best-possible overview of current knowledge and its limitations and underlines the need for a timely generation of stronger evidence in this rapidly expanding field.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
88
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 171 publications
(98 citation statements)
references
References 62 publications
(137 reference statements)
3
88
0
2
Order By: Relevance
“…Although targeted therapy shows great promise, the biggest concern is acquired resistance at which point the therapy loses its efficacy (12). There is limited data in regards to concurrent SABR and targeted therapy, so it is difficult to say at this time if such a treatment course is appropriate for patients without risking undue toxicity from co-administration (13). EGFR inhibitors in particular have been reported to have possibility of pulmonary toxicity which may limit ability to be employed concurrently with radiation therapy (14).…”
mentioning
confidence: 99%
“…Although targeted therapy shows great promise, the biggest concern is acquired resistance at which point the therapy loses its efficacy (12). There is limited data in regards to concurrent SABR and targeted therapy, so it is difficult to say at this time if such a treatment course is appropriate for patients without risking undue toxicity from co-administration (13). EGFR inhibitors in particular have been reported to have possibility of pulmonary toxicity which may limit ability to be employed concurrently with radiation therapy (14).…”
mentioning
confidence: 99%
“…This is further supported by preclinical findings suggesting a radio-sensitizing effect of Vemurafenib [45, 61]. On the other hand, increased side effects such as skin symptoms have been reported for the combination, thus potentially limiting the clinical applicability [1, 29]. Based on these data, BRAF inhibitors should probably be paused during the radiotherapy.…”
Section: Braf Tyrosine Kinase Inhibitorsmentioning
confidence: 68%
“…60,157,158 SBRT is theoretically less systemically immunosuppressive than conventional radiation, in which patients have circulating lymphocytes that may be irradiated over 5 to 6 weeks. 60,126 Early studies have demonstrated that immunotherapy and radiation can safely be administered together and may induce responses, [159][160][161][162] but questions remain regarding the optimal timing of systemic treatment with radiation, radiation dose, and tumour volume irradiated. 60,126,163 Recent work in human sarcomas has suggested that radiation upregulates common targets of recently approved immune checkpoint inhibitors such as PD-L1.…”
Section: Rt and Immunotherapy For Sarcomasmentioning
confidence: 99%